X-ray spectra and light curves of cooling novae and a nova like - Sun, Bangzheng; Luna, Gerardo Juan Manuel (Wiley Blackwell, 2020)
We present X-ray observations of novae V2491 Cyg and KT Eri about 9 yr post-outburst of the dwarf nova and post-nova candidate EY Cyg, and of a VY Scl variable. The first three objects were observed with XMM-Newton, KT Eri also with the Chandra ACIS-S camera, V794 Aql with the Chandra ACIS-S camera and High Energy Transmission Gratings. The two recent novae, similar in outburst amplitude and light curve, appear very different at quiescence. Assuming half of the gravitational energy is irradiated in X-rays, V2491 Cyg is accreting at ˙m = 1.4 × 10-9-10-8 M⊙yr-1, while for KT Eri, ˙m < 2 × 10-10 M⊙ yr. V2491 Cyg shows signatures of a magnetized WD, specifically of an intermediate polar. A periodicity of 39 min, detected in outburst, was still measured and is likely due to WD rotation. EY Cyg is accreting at ˙m ∼ 1.8 × 10-11 M⊙ yr-1, one magnitude lower than KT Eri, consistently with its U Gem outburst behaviour and its quiescent UV flux. The X-rays are modulated with the orbital period, despite the system's low inclination, probably due to the X-ray flux of the secondary. A period of 81 min is also detected, suggesting that it may also be an intermediate polar. V794 Aql had low X-ray luminosity during an optically high state, about the same level as in a recent optically low state. Thus, we find no clear correlation between optical and X-ray luminosity: The accretion rate seems unstable and variable. The very hard X-ray spectrum indicates a massive WD.
Keywords: Ciencias Básicas y Aplicadas; Ciencias Exactas y Naturales; Ciencias Físicas